Daoism and the Project of an Ecological Civilization or Shengtai Wenming 生态文明 - Schönfeld, Martin (Religions, 2019)
For China today, environmentalism is central. The socialist doctrine of "Xi Jinping Thought" prioritizes transitioning to sustainability in the goal of building an "Ecological Civilization". This creates unprecedented opportunities for Daoist practitioners to engage in state-coordinated activism (part 1). We show how the science of the planetary crisis (part 2) resonates with Daoist values (part 3), how these values integrate in national policy goals (part 4), and how this religious environmental activism plays out in case studies (part 5).